The mediating role of body roundness index in the association between dietary inflammatory index and depression: evidence from the US National Health and Nutrition Examination Survey 2007–2023 - Weige Duan; Jian Ma; Shanglan Qu; Jing Zhang; Min Li; Lizhu Jiang (Frontiers in Psychiatry, 2025)
ObjectiveDietary inflammatory index (DII) and body roundness index (BRI) have been reported to be independently associated with an increased risk of depression. The purpose of this study was to examine the mediating role of BRI in the relationship between DII and depression.MethodsA total of 32,210 adults were recruited from the National Health and Nutrition Examination Survey (NHANES; 2007–2023). Depression was assessed with Patient Health Questionnaire-9 (PHQ-9), DII and BRI were calculated for each participant. Weighted multivariate logistic regressions, Spearman’s correlation, and mediation analysis were performed.ResultsA higher DII was significantly associated with an increased risk of depression (OR=1.68, 95% CI: 1.32–2.13, p<0.001). Compared with the lowest quintile (Q1) of BRI, individuals in the highest quintile (Q5) showed a significantly higher risk of depression (OR=1.90, 95% CI: 1.08–3.36, p=0.027). Furthermore, both DII (r=0.071) and BRI (r=0.112) were positively correlated with depressive symptoms, and DII was also positively correlated with BRI (r=0.118), all p<0.001. Of note, BRI partially mediated the relationship between DII and depression (indirect effect 0.002, 95% CI: 0.001–0.003), accounting for 10.7% of the total effect. The mediating effect of BRI was verified in both male and female population.ConclusionsThis study firstly identified a mediating role of BRI in the association between DII and depressive symptoms, suggesting that visceral obesity may be an important pathway through which dietary inflammation affects depression. Our findings may provide evidence-based insights to guide targeted interventions to prevent depression at the population level.